A Literature Based Examination of Human Error in Military Aviation Maintenance Management Programs - AL ARIF, ISMAIL ABDULRAHMAN (2018)
This study examines human error associated with the military aviation maintenance management programs. The rationale behind this study was based on the rising human error that comes along with military aviation maintenances. To come up with a practical findings quantitative data were obtained by consulting military aviation technicians at MRO (Maintenance Repair and Overhaul) headquarters in Abu Dhabi, United Arab Emirates. The main data collection tool that was used for this study was questionnaires subdivided into two sections examining demographics of the respondents alongside the objectives. The results indicate that military aviation the industry is faced with fuel and the labor costs challenges that significantly contribute to human error in the management program. Neglect and less focus on the product as well as machine safety together with complexities such as poor training enhances errors in the military aviation programs. The study finally draws to conclusion that there are varied human error associated with the military aviation maintenance management programs most of which can be mitigated.